PREVALENCE OF MALNUTRITION AMONG SCHOOL GOING CHILDREN: A REVIEW - Pradipta Singha; Indrajit Karmakar; Jagannath Ghosh (The Bioscan, 2024)
Malnutrition among school-going children has been observed as a pressing global issue, with significant prevalence rates in various regions. A study conducted in Nepal’s Dang district revealed that 25.7% of adolescents were malnourished, where underweight was the most common form. Factors such as religion, family type, and dietary habits were the influencing factors of malnutrition. In Bangladesh's haor areas, approximately half of the primary school children were found to be wasted, underweight, or stunted. In that study higher prevalence rates were found among girls. Age, family size, and timely introduction of complementary foods are some more additions in the influencing factors of malnutrition rates. Meanwhile, in India, a study among boys aged 5-18 showed low body weight, height, and BMI compared to international references, with 10% of boys being undernourished. To tackle this high prevalence rates of malnutrition among school and children proper nutrition education, support for parents, and targeted interventions are crucial.